2019
DOI: 10.1111/bjh.16337
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome evaluation of medium/high risk acute lymphoblastic leukaemia children treated with or without cranial radiotherapy in the EORTC 58832 randomized study

Abstract: We investigated the long-term outcome, the incidence of second neoplasms (SN) and the rate of late adverse effects (LAE) in children with central nervous system (CNS) negative medium/high-risk de novo acute lymphoblastic leukaemia (ALL), in first complete remission (CR1) at end of late intensification, randomized to receive no cranial radiotherapy (No CRT, n = 92) versus CRT (standard arm, n = 84) in the non-inferiority EORTC 58832 study (1983)(1984)(1985)(1986)(1987)(1988)(1989). Median follow-up was 20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The use of XRT has become contentious because of its late adverse effects [1]. We have shown previously that cranial XRT failed to provide any benefit to medium-and high-risk patients having received high-dose methotrexate (HD MTX) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The use of XRT has become contentious because of its late adverse effects [1]. We have shown previously that cranial XRT failed to provide any benefit to medium-and high-risk patients having received high-dose methotrexate (HD MTX) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The latter finding could partly be explained by the relatively low proportion of patients treated with cranial radiotherapy or bone marrow/hematopoietic stem cell transplantation in EORTC protocols compared to other treatment protocols 12–18,37,38 . Indeed, following the results of the randomized EORTC trial 58,832 (no increase in the incidence of CNS relapse in patients randomized without cranial radiotherapy), the EORTC was the first group to omit cranial radiotherapy as first‐line treatment for all patients with childhood ALL 39,40 . In the same study, the evaluation of long‐term side effects showed that the omission of cranial radiotherapy was associated with a lower incidence of second neoplasms and a lower rate of late CNS and endocrine adverse events 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, following the results of the randomized EORTC trial 58,832 (no increase in the incidence of CNS relapse in patients randomized without cranial radiotherapy), the EORTC was the first group to omit cranial radiotherapy as first‐line treatment for all patients with childhood ALL 39,40 . In the same study, the evaluation of long‐term side effects showed that the omission of cranial radiotherapy was associated with a lower incidence of second neoplasms and a lower rate of late CNS and endocrine adverse events 40 . Among the three EORTC studies included in the present QoL evaluation, bone marrow/hematopoietic stem cell transplantation was only indicated for “very high‐risk” patients included in EORTC study 58,881, in first complete remission and with an available donor.…”
Section: Discussionmentioning
confidence: 99%
“…The likely explanation of this result is the occurrence of neurocognitive sequelae (Krull, Brinkman, & Li, 2013 ). We previously evaluated the long‐term outcomes of the randomised question comparing No CRT versus CRT in medium/high‐risk ALL patients included in study 58832 and reported cognitive disturbance in 18.8% of the patients in the No CRT arm versus 42.1% in the CRT arm (Piette et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%